2021
DOI: 10.1142/s1088424621500875
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetricallymeso-substituted porphyrin derivative containing the triazole group: Synthesis, characterization and photo-physicochemical properties

Abstract: In this study, a novel asymmetrically meso-substituted AB3 porphyrins derivative including one triazole group to enhance the anticancer activity of the molecule and three bromophenyl groups to improve photochemical properties has been synthesized and characterized. Our objectives were to generate a system with triazole and bromophenyl groups that enhance the singlet oxygen generation and exhibits an anti-cancer effect. Therefore, photophysical and photochemical properties of this asymmetric porphyrin derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…33 An asymmetrical AB 3 -type porphyrin having one triazole and three bromophenyl groups has been recently reported by our group. 25 It was revealed from the study that the AB 3 -type porphyrin motif showed no aggregation tendency, solubility in common organic solvents and a high singlet oxygen quantum yield. 25…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…33 An asymmetrical AB 3 -type porphyrin having one triazole and three bromophenyl groups has been recently reported by our group. 25 It was revealed from the study that the AB 3 -type porphyrin motif showed no aggregation tendency, solubility in common organic solvents and a high singlet oxygen quantum yield. 25…”
Section: Introductionmentioning
confidence: 99%
“…25 It was revealed from the study that the AB 3 -type porphyrin motif showed no aggregation tendency, solubility in common organic solvents and a high singlet oxygen quantum yield. 25…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations